Assessment of Gender Based Difference in Occurrence of Periodontal Diseases: A Retrospective Study - SHAH, PALAK MAYUR; RAJASEKAR, ARVINA; CHAUDHARY, MANJARI (The journal of contemporary issues in business and government, 2021)
Gingivitis is defined as the inflammation of the soft tissues of the oral cavity, without the apical migration of the junctional epithelium. Periodontitis is an inflammatory condition which affects the soft tissues leading to the apical migration of the junctional epithelium. The aim of the study was to assess the gender based difference in the occurrence of periodontal diseases. A retrospective study was conducted using the case records of patients in a private institution between June 2019 to March 2020. A total of 4000 patients were recruited. The study participants were divided into 2 based on gender (Group 1 - 2000 males, Group 2 - 2000 females). Data regarding the periodontal status of the patients were collected from their records. Descriptive and inferential statistics were done using SPSS software. Prevalence of periodontitis was higher among males (31.08%) when compared to females (27.28%). Prevalence of gingivitis was higher in females (22.73%) when compared to males (18.93%). There was a statistically significant association between the gender and periodontal disease (p<0.05). Also, the prevalence of periodontitis was higher among the age group of 56-65 years (19.38%) and gingivitis was higher among the age group of 15-25 years (19.85%). There was a statistically significant association between age and periodontal disease (p<0.05). The finding of the present study showed that prevalence of periodontitis was higher in males when compared to females.